2001
DOI: 10.1021/ja010648r
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Photosubstitution Reactions of Fe(CO)5:  An Ultrafast Infrared Study of High Spin Reactivity

Abstract: The photosubstitution reactions of Fe(CO)5 with alcohols and triethylphosphine have been studied in room temperature solution using femtosecond UV pump IR probe techniques. The dynamics of Fe(CO)5 in alcohols show that the coordination of the hydroxyl group of the solvent with triplet Fe(CO)4 is generally much faster than the coordination timescale observed with comparable singlet species. The physical reason for this is the fact that the metal C−H agostic bond is much weaker for triplets, thus allowing fast r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(131 citation statements)
references
References 40 publications
8
116
1
Order By: Relevance
“…251,252 It is well known that singlet Fe(CO)4 is highly reactive and capable of ligand addition with a number of common organic compounds: alkanes, alkenes, alcohols, alkylphosphines, and alkylsilanes. [251][252][253][254][255] This reactivity arises from the electron deficiency at the metal centre of Fe(CO)4 and the lack of steric hindrance with the solvent, making it a strong electrophile.…”
Section: Fe(co)5mentioning
confidence: 99%
“…251,252 It is well known that singlet Fe(CO)4 is highly reactive and capable of ligand addition with a number of common organic compounds: alkanes, alkenes, alcohols, alkylphosphines, and alkylsilanes. [251][252][253][254][255] This reactivity arises from the electron deficiency at the metal centre of Fe(CO)4 and the lack of steric hindrance with the solvent, making it a strong electrophile.…”
Section: Fe(co)5mentioning
confidence: 99%
“…16,17,19,[22][23][24][25]27 Indeed, all the CO ligand vibrational mode frequencies were predicted by DFT calculations to redshift by an average of 6 cm -1 relative to those of 1 when simulations were performed on a MeCN molecule coordinating via its nitrogen atom lone pair as a solvent adduct to the vacant site on the Fe after CO loss (see SI, Fig. S5).…”
Section: Comparison Of Different Uv/vis Wavelengths and Solventsmentioning
confidence: 99%
“…[20][21][22][23][24] More recently, ultrafast studies on the photochemistry of Fe(CO) 5 in solution have been pushed into the x-ray domain and an Fe K-edge x-ray absorption study was reported by Rose-Petruck and co-workers, 25 while Wernet et al 26,27 implemented femtosecond Fe L 3 -edge resonant inelastic xray scattering (RIXS) at the x-ray Free Electron Laser in Stanford. RIXS, which is a variant of x-ray emission spectroscopy, is a sensitive probe of the spin state of molecular systems.…”
Section: Introductionmentioning
confidence: 99%